Paragorgia arborea Linnaeus 1758 - JUAN ARMANDO SÁNCHEZ (Zenodo, 2005)
Paragorgia arborea (Linnaeus, 1758) (Figs. 6–9) Alcyonium arboreum Linnaeus 1758: 803. Paragorgia nodosa Koren & Danielsen 1883 (sensu Bayer 1956: 70). Paragorgia pacifica Verrill 1922: G16. Paragorgia arborea : Broch 1912: 6; Grasshoff 1979: 117 (and references therein). Material examined: NIWA 3308, 33°55.6’S – 167°55.1’E, 1225 m, ( Waipori , bottom trawling, Z10987), 23 January 2002, New Zealand; NIWA 3309, (J217), 33°55.6’S – 167°54.4’E, 955 m, ( Waipori 1621/011, Z11009) 8 June 2002; NIWA Z10920 (J208)/ Z10956 (J212), (AEX 0101/080), New Zealand EEZ, exact locality unknown (probably near: 42°47’S – 179°32’E, 1077 m), ( Kap Farval ), 17 October 2001; NIWA 3310, Z9862 (J219), 44° 45.0S –174°50.0–49.0’E, 687–940 m, ( Kap Farval 1278/102), 21 October 1999, New Zealand; NIWA 3311, X700 (J221), 35° 50.447’–49.900’S–177° 54.497–54.644’E, “Southern Havre trough” (dredge), 1525–1798 m, 12 February 1996, New Zealand; USNM 98045, 52° 17’– 52° 22’S –160° 40’– 160° 34’E, 659–798 m, ( Eltanin R/ V 1414, USAP 16, U. Southern California, trawlblake), 9 February 1965, New Zealand; USNM 52433, 54° 19’N – 159° 40’ W, ( Albatross R/V 3338), 1143 m, 28 August 1890, Alaska, USA; USNM 1014919, Davison seamount, 1313 m, California 2003, USA. Diagnostic characters. Surface cortex (including calyx surface) containing small, ornate, radiate sclerites (6, 7, and 8 rays); predominantly 6 radiates with distinctive, labyrinthlike, groove markings in the radiate projections or ornamentations (Figs. 7 C–D and 8C–D). Description. Robust treelike colonies up to several meters in height with bubblelike concentrations of autozooids (Fig. 6). Complete specimens exhibiting dense and regular accumulations of autozooid nodules or bulbs on distal or lateral branches, whereas the distal main stem and branches are usually without nodules (Fig. 6 A). Internodular surface with numerous and uniformly distributed tiny siphonozooid apertures giving the colony a granular texture (Fig. 6 D). Medulla perforated by 5–7 main stem canals in terminal ...